Implementation of National Medium Term Development Plan (RPJMN) of the Nawacita Program in Improving Good Governance - Purnama, Sena Aji; Bestari, Prayoga (Journal of International Conference Proceedings, 2020)
The Nawacita program, which is contained in National Medium-Term Development Plan (RPJMN), must be supported and realized by local governments, both Provinces and Cities / Regencies, since Nawacita is a national agenda for a more advanced, just and prosperous Indonesia. All policies issued by the Central Government must be supported by the Regional Government in implementing its vision and mission, must be able to go hand in hand with the Nawacita program to achieve national goals. The appropriate method used for this research is descriptive study with a qualitative approach. Cianjur Regency is a regency in West Java province and not too far from Jakarta as the capital and centre of Indonesian government. To implement the Nawacita program in Cianjur Regency, local governments are obliged to optimize the performance of institutions, all government processes are intended to serve all interested parties and good governance should bridge different interests for the development and achievement of national goals.